2013
DOI: 10.1111/jnc.12318
|View full text |Cite
|
Sign up to set email alerts
|

Monitoring progression in Friedreich ataxia (FRDA): the use of clinical scales

Abstract: Friedreich ataxia (FRDA) is a progressive neurodegenerative disorder associated with ataxia, dysarthria, pyramidal tract signs, sensory loss, cardiomyopathy and diabetes. There is no cure for FRDA so far. Studies of the natural history of the disease and future therapeutic trials require development of appropriate outcome markers. Since any therapeutic benefit is expected to modulate deterioration over time rather than to reverse disability, potential outcome measures must be sensitive instruments carefully an… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

2
42
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
9

Relationship

0
9

Authors

Journals

citations
Cited by 54 publications
(44 citation statements)
references
References 36 publications
2
42
0
Order By: Relevance
“…Automated gait analysis provides multiple measures of gait that are relevant to the clinical ataxia rating scales such as the Friedreich Ataxia Rating Scale (Burk, Schulz, & Schulz, 2013). All four feet are measured individually in addition to cadence measurements, step patterns, and regularity indices.…”
Section: Discussionmentioning
confidence: 99%
“…Automated gait analysis provides multiple measures of gait that are relevant to the clinical ataxia rating scales such as the Friedreich Ataxia Rating Scale (Burk, Schulz, & Schulz, 2013). All four feet are measured individually in addition to cadence measurements, step patterns, and regularity indices.…”
Section: Discussionmentioning
confidence: 99%
“…The quantitative timed activities include the 25-foot walk, 9-hole peg test, and PATA speech rate. Studies have demonstrated the validity of the FARS in the evaluation of FRDA patients [10,11]. …”
Section: Frda Clinical Rating Scalesmentioning
confidence: 99%
“…The severity of the ataxia symptoms and disease progression may be measured periodically by a number of assessment instruments, such as the International Cooperative Ataxia Rating Scale (ICARS), the Scale for the Assessment and Rating of Ataxia (SARA), and the Friedreich Ataxia Rating Scale (FARS) [17,18]. FRDA progression is extremely variable, in accordance with the symptoms' age of onset.…”
Section: Disease Progressionmentioning
confidence: 99%